Two-Year Clinical Follow-Up Assessment of the Novel Cingular Surgical Bovine Pericardial Valve - Chen, Jinmiao; Lv, Minzhi; Lu, Yuntao; Fu, Jiahui; Guo, Yingqiang; Tao, Liang; Zhou, Xinmin; Gu, Tianxiang; Wei, Lai; Hong, Tao; Wang, Chunsheng (Frontiers in Cardiovascular Medicine, 2021)
Objectives: To evaluate the 2-year clinical safety and hemodynamic outcomes of the Cingular bovine pericardial bioprosthesis. Methods: A prospective, multi-center, single-arm trial was conducted in patients who required aortic or mitral valve replacement. From March 2016 to October 2017, 197 patients were implanted with the Cingular bovine pericardial valve at five sites in China. The clinical outcomes and hemodynamic performance were assessed through 2-year follow-up. Clinical safety events were reviewed by an independent Clinical Events Committee, and echocardiographic data were assessed by an independent Core Laboratory. Results: The mean age was 66.9 ± 4.9 years. The 2-year survival rate was 96.4%. A complete 2-year clinical follow-up was achieved in 189 of 190 survivors. No case of structural valve deterioration, major perivalvular leak, prosthetic valve endocarditis or valve-related reoperation was seen. For the aortic valve, the mean pressure gradient observed was 12.5 ± 4.0 mm Hg and the effective orifice area (EOA) was 2.0 ± 0.3 cm2. For the smaller size aortic valves, 19mm and 21mm, respective mean EOA values of 1.7 ± 0.2 cm2 and 1.8 ± 0.2 cm2 were found. The values for mean pressure gradient and mean EOA for mitral bioprostheses were 4.0 ± 1.4 mm Hg and 2.2 ± 0.3 cm2, respectively. There was no significant change between 1-year and 2-year hemodynamic performance. Conclusions: The Cingular bovine pericardial valve showed favourable clinical safety and hemodynamic outcomes over 2-year follow-up. Further follow-up is required to validate the long-term durability.